Study to evaluate outcome of autologous fat grafting for facial scar and deformities - Dr. Kabita Kalita, Dr Gangamma K, Dr. Dibyajyoti Bora, Dr. Poresh Boruah, Dr. Jyotirmay Baishya (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Facial scars and deformities pose significant aesthetic and psychosocial challenges,often inadequately addressed by conventional modalities. Autologous fat grafting (AFG) has emergedas a minimally invasive technique offering both volumetric correction and regenerative benefits due to the presence of adipose-derived stem cells